Casting a New Manufacturing Gameplan Thru ‘Make in India’ - Thareja, Priyavrat (Journal of Advanced Research in Mechanical Engineering and Technology, 2019)
To support the making of a powerful India, an initiative titled “Make in India” was instituted in 2014 duly complimented by National Manufacturing policy. This paper reviews the various imperatives and challenges, along with the success levels in light of Make in India, and measures in terms of the relationship of Manufacturing (growth) to GDP. The various manufacturing options are classified, and a case is raised for preferences of founding as a dominant manufacturing process, in view of the capability for complex products, through its attributes or thru’ flexibility. The challenges and constraints, if any, are also discussed. Thus, Grounded over the exquisite competence of founding, the paradigm of ‘Cast in India’ is proposed. For a competitive benchmarking the case of China is considered. How to cite this article: Thareja P. Casting a New Manufacturing Gameplan Thru ‘Make in India’. J Adv Res Mech Engg Tech 2019; 6(1&2): 4-12.